Clinical, pathological, and therapeutic features of newly diagnosed prostate cancer predominantly detected by opportunistic PSA screening: A survey of Shiga Prefecture, Japan. Issue 15 (21st August 2021) - Okinaka, Yuki; Kageyama, Susumu; Nishizawa, Koji; Yoshida, Toru; Ishitoya, Satoshi; Shichiri, Yasumasa; Kim, Chul Jang; Iwata, Tsuyoshi; Yokokawa, Ryusei; Arai, Yutaka; Nishikawa, Zenkai; Soga, Hiroki; et al.
Abstract: Background: In all the prefectures of Japan, with the exception of Shiga Prefecture, more than half of local governments have an organized prostate‐specific antigen (PSA) screening system in place. However, in the Shiga Prefecture, only a single city performed PSA screening over the time period of this survey. The purpose of the present study was to determine the clinical, pathological, and therapeutic features of newly diagnosed prostate cancer in localities where a formally organized screening system was almost entirely absent. Methods: A multicenter observational study was conducted in the Shiga Prefecture, which has the lowest rate of population‐based PSA‐screening in Japan. Patients' age, initial PSA, reasons for PSA testing, Gleason score, clinical stage, and primary treatments were surveyed. We stratified patients according to the reasons for PSA measurement, and compared the differences between groups subject to organized versus opportunistic screening. Results: In the 2 years 2012 and 2017, 984 newly diagnosed prostate cancer patients were analyzed. Of these, 954 (97%) were opportunistically tested (i.e., not as part of an organized screening system), with the remaining 29 (3%) measured as part of an organized screening program. Patients in the former group exhibited a higher initial PSA value than in the organized screening group (median: 11.49 vs. 5.67 ng/ml). They also had worse clinical features, including higher Gleason score and TNM stage. More patients in the organized screening group were treated curatively than in the nonorganized screening group in terms of the primary treatment. The results were similar in a subanalysis of the patients of age 50–69 years. Conclusions: Organized PSA screening contributes to increasing the number of patients diagnosed with early‐stage cancer who can be treated curatively.